O góralskim humorze - Mlekodaj, Anna (Zeszyty Wiejskie, 2014)
The article begins with a short presentation of the state of research regarding humor and comedy. Humor is the process which activates subjects and discusses social functions. Next, past and present theories on the topic of comedy (the comedic effect) created, for example, by philosophers and psychologists are characterized. They all emphatically confirm that the conditions for the existence of comedic word are through the recipient’s ability to perceive comedy. The second part of the article is dedicated to the analysis of humor mechanisms in dialectical texts from the Podtatrza region. The highlander’s previous sense of humor came through songs, classified by researchers (Sadownik) as comedy. The most frequent mechanism of humor in these works was touching on taboo topics, justified through concrete give-and-take situations. Furthermore, the article is dedicated to the analysis of the appearance of humor in the poetry of Wanda Czubernatowa, Zdzisław Barglik, in the stories of Sabała, the tales of Andrzej Skupień Florek, Józef Pitorak, Józef Pitoń and Irena Grobarczyk (in Orawa). The proposals illustrate the important role of dialect in building comedy even though as compared to the Polish language, it is limited in terms of linguistic wit. The author sees the cause of this in the drop in use of the regional dialect which, in the long run, contains two advantages in building humor: conciseness and accuracy.